If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + 4) = y + 36 Reorder the terms: 5(4 + y) = y + 36 (4 * 5 + y * 5) = y + 36 (20 + 5y) = y + 36 Reorder the terms: 20 + 5y = 36 + y Solving 20 + 5y = 36 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 20 + 5y + -1y = 36 + y + -1y Combine like terms: 5y + -1y = 4y 20 + 4y = 36 + y + -1y Combine like terms: y + -1y = 0 20 + 4y = 36 + 0 20 + 4y = 36 Add '-20' to each side of the equation. 20 + -20 + 4y = 36 + -20 Combine like terms: 20 + -20 = 0 0 + 4y = 36 + -20 4y = 36 + -20 Combine like terms: 36 + -20 = 16 4y = 16 Divide each side by '4'. y = 4 Simplifying y = 4
| .5x+2=-2 | | 7x+5-6x=23 | | 5-3(x-1)=2x-(x+4) | | 3x-5+5x=52 | | .5x+2=0 | | x-16+16=79+16 | | 1-3x+5x=17 | | 6x-2=4+3x-2 | | (2n)(4n+2)= | | X+2(3.5)=7 | | 1+5x-3x=-17 | | .5x+2=1 | | 0.3n=0.2 | | 9+6x-3x=36 | | 2x+2=96 | | 13=1-2x-2x | | 4x-3-2x=-3 | | 26=3c-3(6-2c) | | Vf=vi+(9.81)6 | | 4x-5=-19 | | 7x+1-2x=41 | | 2x^2-4x+6y-10=0 | | -27+6d=7(4d+8) | | 8+4x-3x=-2 | | 13x-31+8x-176=180 | | rt-2n=fort | | 3x-4(x+3)=22 | | 2(y+5)=y+13 | | 23=4x-x-10 | | (10x^2)+3=11x | | -3(n-6)=12(n-4)+7n | | 12y-15y=584 |